2021
DOI: 10.1111/liv.14833
|View full text |Cite
|
Sign up to set email alerts
|

Is hepatitis delta underestimated?

Abstract: Hepatitis D virus may be underestimated because it is a significant problem in HBsAg‐positive patients, especially those who inject drugs, have HIV or HCV co‐infections and/or live in certain endemic regions. In the past few decades, the prevalence of HDV was expected to have decreased as a result of improvements in public healthcare policies and universal HBV vaccination programs. However, HDV has continued to spread in low‐income countries, with local outbreaks and migration to less endemic areas, so that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
(65 reference statements)
0
16
0
Order By: Relevance
“… 22 both describe considerably higher prevalence among hepatology clinic attendees, at 16.4% and 13.02%, respectively. This discrepancy may be a result of meta-analyses study selection 12 or screening bias among the Canadian clinic population, but the publicly funded healthcare system in Canada may also influence the prevalence findings. It is plausible that access to universal healthcare may result in a relatively lower ratio of HBV-referred patients having severe liver disease at the time of referral.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 both describe considerably higher prevalence among hepatology clinic attendees, at 16.4% and 13.02%, respectively. This discrepancy may be a result of meta-analyses study selection 12 or screening bias among the Canadian clinic population, but the publicly funded healthcare system in Canada may also influence the prevalence findings. It is plausible that access to universal healthcare may result in a relatively lower ratio of HBV-referred patients having severe liver disease at the time of referral.…”
Section: Discussionmentioning
confidence: 99%
“… 11 The true prevalence and distribution of HDV seroprevalence and active infection is uncertain, with estimates that vary significantly. 12 , 13 One study established a global HDV prevalence estimate at 12 million infected individuals, 14 or approximately 4.5% of HBsAg-positive individuals. Canada has an estimated HBV infection rate of approximately 13.4 per 100,000 (2017 data 15 ) with >250,000 chronically infected Canadians living with HBV.…”
Section: Introductionmentioning
confidence: 99%
“…4 In such an uncertain epidemiological status, the epidemiology of hepatitis D virus (HDV) is even more undefinable, as HDV screening rates among diagnosed hepatitis B surface antigen (HΒsAg) positive individuals seem to vary widely usually ranging at low levels even in epidemiologically well organized countries. 5,6 Thus, the global HDV prevalence has been debatable and was declared uncertain by the 2017 WHO Global Hepatitis Report. 7 The global prevalence of HDV infection, which is usually based on the detection of antibodies against HDV (anti-HDV), has been reported to vary widely in the estimations of different systematic reviews, 5 since the global number of HDV infected individuals has been suggested to range from 12 to more than 60 millions.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Thus, the global HDV prevalence has been debatable and was declared uncertain by the 2017 WHO Global Hepatitis Report. 7 The global prevalence of HDV infection, which is usually based on the detection of antibodies against HDV (anti-HDV), has been reported to vary widely in the estimations of different systematic reviews, 5 since the global number of HDV infected individuals has been suggested to range from 12 to more than 60 millions. [8][9][10] At the same time, it is well accepted that HDV underdiagnosis remains • Anti-HDV prevalence varies throughout Greece being higher in patients born abroad with younger age, parenteral drug use and advanced liver disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation